2017
DOI: 10.3892/ijo.2017.4215
|View full text |Cite
|
Sign up to set email alerts
|

Arctigenin induces the apoptosis of primary effusion lymphoma cells under conditions of glucose deprivation

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) is the causative agent of primary effusion lymphoma (PEL) and Kaposi's sarcoma. PEL is a type of non-Hodgkin's B-cell lymphoma, affecting immunosuppressed individuals, such as post-transplant or AIDS patients. However, since PEL is resistant to chemotherapeutic regimens, new effective treatment strategies are required. Arctigenin, a natural lignan compound found in the plant Arctium lappa, has been widely investigated as a potential anticancer agent in the clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Apoptosis is an important way of the cell biological process, and inducing apoptosis has also become the modern way of treating cancers. The study found that ARG induced apoptosis of primary exudative lymphoma cells in the absence of glucose and induced apoptosis of colon cancer cells through the ROS/p38MAPK pathway [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is an important way of the cell biological process, and inducing apoptosis has also become the modern way of treating cancers. The study found that ARG induced apoptosis of primary exudative lymphoma cells in the absence of glucose and induced apoptosis of colon cancer cells through the ROS/p38MAPK pathway [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…PEL patients typically have less than 1 yr survival time even with aggressive chemotherapy [40]. Many other drugs and natural products have been reported to inhibit PEL cell growth and tumorigenesis [35,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. However, even though KSHV is known to drive this cancer, at present there are no inhibitors that selectively and effectively target KSHV gene products.…”
Section: Discussionmentioning
confidence: 99%
“…As shown under the table, the IC50 values of eleven compounds were distributed between 0.2 and 10.2 µM, respectively. Baba et al identified that apoptosis of primary effusion lymphoma (PEL) cells such as BC3, Ramos, BCBL1, and DG75 was induced under glucose-free conditions by arctigenin-a natural compound which has been studied for various bioactivity [34]. Arctigenin increased c-caspase-3, -9, and cleaved poly ADP ribose polymerase (c-PARP) in BC3, and triggered dissipation of mitochondrial membrane potential (MMP) together with decreased ATP production in BC3 and Ramos.…”
Section: Microorganism-derived Compounds and Lymphomamentioning
confidence: 99%